On-Farm Data Security: Practical Recommendations for Securing Farm Data - Hazrati, Mehdi; Dara, Rozita; Kaur, Jasmin (Frontiers in Sustainable Food Systems, 2022)
The growth in the use of Information and Communications Technology (ICT) and Artificial intelligence (AI) has improved the productivity and efficiency of modern agriculture, which is commonly referred to as precision farming. Precision farming is strongly dependent on collecting a large amount of data from farms. Despite the many advantages of precision farming, security threats are a major challenge which is continuously on the rise and can harm various stakeholders in the agricultural systems. These security issues may result in security breaches that could lead to unauthorized access to farmers’ confidential data, identity theft, reputation loss, financial loss, or disruption to the food supply chain. Security breaches can occur because of an intentional (e.g., insider attack) or unintentional (e.g., accidental data leakage) action or incident. Research suggests that humans play a key role in causing security breaches due to errors or system vulnerabilities. Farming is no different from other sectors. There is a growing need to protect data and IT assets on farms by raising awareness, promoting security best practices and standards, and embedding security practices into the systems. This paper provides recommendations for farmers on how they can mitigate potential security threats in precision farming. These recommendations are categorized into human-centric solutions, technology-based solutions, and physical aspect solutions. The paper also provides recommendations for Agriculture Technology Providers (ATPs) to alleviate the security risks.